Analgesic Drug Prescription Patterns on Five International Paediatric Wards - Botzenhardt, Sebastian; Rashed, Asia N.; Wong, Ian C. K.; Tomlin, Stephen; Neubert, Antje (Paediatric Drugs, 2016)
AIM: Analgesic and anti-inflammatory drugs are frequently prescribed in paediatrics. Prescribing and dosing patterns in hospitalised children are not well known. This study explores analgesic drug utilisation on five paediatric wards and discusses its findings in comparison with World Health Organization (WHO) guidelines. METHOD: A sub-analysis of a prospective, multicentre, observational cohort study was undertaken. Prescription data of children aged up to ≤18 years were collected between October 2008 and December 2009 on paediatric general medical wards in five hospitals in Australia, Germany, the United Kingdom (UK), Hong Kong (HK) and Malaysia. Analgesic drug prescriptions were analysed for prescribing patterns in terms of dosing, frequency and route of administration. Dosing data were compared with local recommendations and WHO guidelines for children. RESULTS: In the study cohort, 56.8 % (726/1278) of paediatric patients received at least one analgesic drug prescription (1227 prescriptions). The median age of patients with analgesics was 2.2 years [interquartile range (IQR) 0.8-7.3], and the median number of prescriptions per patient was one (IQR 1-2). The most commonly prescribed drugs were oral paracetamol (45.9 %, 563/1227) and oral ibuprofen (19.9 %, 244/1227). Daily doses of paracetamol ranged from 30 mg/kg/day in Germany to 67-68 mg/kg/day in the UK and HK (p < 0.05). For ibuprofen, single doses ranged from 5-6 mg/kg in HK and the UK to 10 mg/kg in Germany and Australia (p < 0.001). Opioid use prevalence was statistically different between the centres and ranged from 0 to 17.6 % (p < 0.001). CONCLUSION: This study provides a comprehensive overview of analgesic drug use of hospitalised children. Similar to primary care data, paracetamol is the most commonly used analgesic. As recommended by WHO guidelines, oral medication was favoured and opioids used in addition to paracetamol and ibuprofen. Overall drug utilisation was in line with local recommendations and WHO guidelines. Differences in use of paracetamol and ibuprofen among countries were seen, indicating that safety concerns are perceived differently. More large-scale safety studies are needed.
EVALuna2:34010

Drug Utilisation and Off-Label Use on a German Neonatal Intensive Care Unit: A Retrospective Cohort Study and 10-Year Comparison - Geißler, Carmen; Schulze, Christopher; Botzenhardt, Sebastian; Rascher, Wolfgang; Neubert, Antje (Pharmacy, 2020)
Pharmacotherapy of neonates is complex and marked to a large extent of off-label use. The implementation of the Paediatric Regulation (2007) gave hope for a change in the safety and efficacy for drugs used in neonatal intensive care units (NICU). This study investigates drug utilisation patterns and off-label use in a German neonatal intensive care unit (NICU) in 2014. A 12-months retrospective, observational cohort study was performed at the NICU of the University Children's Hospital Erlangen, Germany. Licensing status was determined using the Summary of Product Characteristics (SmPC). Results are compared with a similar study conducted 10 years earlier. The study included 204 patients (57.8% male) (2004: 183) and 2274 drug prescriptions were recorded (2004: 1978). The drugs that were mostly prescribed were drugs for the nervous system (2004: 22.6%; 2014: 26.9%) and anti-infectives for systemic use (2004: 26.0%; 2014: 24.9%);34.3% (2004) and 39.2% (2014) of all prescriptions were off-label;62.7% of all patients received at least one off-label or unlicensed drug (2004: 70%). For 13 drugs, the licensing status changed either from off-label to label (n = 9) or vice versa (n = 4). Overall, there was no significant change neither in terms of the drugs used nor regarding their licensing status. Further studies are needed to validate these findings in a European context.
CRIS-Team WoS Importer:2020-10-30

Impact of a computerized physician order entry system on medication safety in pediatrics-The AVOID study - Wimmer, Stefan; Toni, Irmgard; Botzenhardt, Sebastian; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmacology Research and Perspectives, 2023)
BACKGROUND: One of the most critical steps in the medication process on pediatric wards is the medical prescription. This study aims to investigate the impact of a computerized physician order entry (CPOE) system on Adverse Drug Events (ADEs) and potentially harmful ADEs (pot ADEs) in comparison with paper-based documentation in a general pediatric ward at a German University hospital. METHODS: A prospective pre-post study was conducted. All patients aged 17 years or younger were observed during the study periods (5 months pre- and postimplementation). Issues Regarding Medication (IRM) were identified by intensive chart review. Events were assessed regarding causality (WHO), severity (WHO; Dean & Barber for MEs), and preventability (Shumock) and classified into (pot) ADEs, (pot) Medication errors (ME), Adverse drug Reactions (ADR), and Other incidents (OI) accordingly. RESULTS: Total of 333 patients with medication were included in the paper-based prescribing cohort (phase I) and 320 patients with medication in the electronic prescribing cohort (phase II). In each cohort, patients received a median number of four different drugs (IQR 5 and IQR 4). A total of 3966 IRM was observed. During the hospitalization, 2.7% (n = 9) patients in phase I and 2.8% (n = 9) in phase II experienced an ADE. Potentially harmful MEs were less often observed in the cohort with electronic prescribing (n = 228 vs. n = 562). The mean number per patient significantly decreased from 1.69 to 0.71 (p < .01). CONCLUSION: The implementation of a CPOE system resulted in a reduction of issues regarding medication, particularly MEs with the potential to harm patients decreased significantly.
CRIS-Team Scopus Importer:2023-06-02
Keywords: adverse drug event; adverse drug reaction; computerized physician order entry; electronic prescribing; medication error; medication safety; pediatrics

Long-term safety of deferiprone treatment in children from the Mediterranean region with beta-thalassemia major: the DEEP-3 multi-center observational safety study - Botzenhardt, Sebastian; Felisi, Mariagrazia; Bonifazi, Donato; Del Vecchio, Giovanni C.; Putti, Maria C.; Kattamis, Antonis; Ceci, Adriana; Wong, Ian C. K.; Neubert, Antje (Haematologica, 2018)
EVALuna2:35838

Safety Profile of Oral Iron Chelator Deferiprone in Chinese Children with Transfusion-Dependent Thalassaemia - Botzenhardt, Sebastian; Sing, Chor W; Wong, Ian C K; Chan, Godfrey Chi-Fung; Wong, Lisa Y L; Felisi, Mariagrazia; Rascher, Wolfgang; Ceci, Adriana; Neubert, Antje (Current Drug Safety, 2016)
UNLABELLED: There is a lack of knowledge regarding the incidence of serious adverse drug reactions (ADR) to the oral iron chelator deferiprone in Chinese children with transfusion-dependent thalassaemia. In this retrospective population-based cohort study, paediatric thalassaemia patients in Hong Kong were screened for serious and medically important adverse events related to deferiprone therapy using diagnosis codes, laboratory data and hospital admissions. Potential ADRs were assessed by reviewing concomitant medications, diagnoses and laboratory data and evaluated using standardised causality assessment. Eighty-seven patients contributing 169.8 person-years were included. Thirty ADRs were identified in 21 patients. Most ADRs (56.0%) occurred in the first three months of therapy. Neutropenia occurred in 11 patients (12.6%; incidence rate 6.5 per 100 patient-years) and severe neutropenia (agranulocytosis) was observed in 5 patients (5.7%, incidence rate 2.9 per 100 patient-years). Other identified ADRs involve severe arthropathy, elevated liver enzymes and mild thrombocytopenia. In conclusion, the safety profile of DFP therapy in Chinese children suffering from transfusion-dependent thalassaemia is in line with previous studies of non-Chinese children. However, unlike previous studies, we observed a relatively high incidence of agranulocytosis and neutropenia in patients with simultaneous combined therapy. Hence close monitoring for white blood cell counts is advised in Chinese children under combined iron chelation therapy. Further prospective clinical and pharmacogenetic studies are required to better evaluate this important safety signal. KEY POINTS: • Half of the identified ADRs related to deferiprone therapy occurred during the first three months of treatment. • A relatively high incidence of agranulocytosis and neutropenia. Hence close monitoring for white blood cell counts is advised in Chinese children under combined iron chelation therapy.
EVALuna2:34001

Safety profiles of iron chelators in young patients with haemoglobinopathies - Botzenhardt, Sebastian; Li, Niya; Chan, Esther W.; Sing, Chor Wing; Wong, Ian C. K.; Neubert, Antje (European Journal of Haematology, 2017)
BACKGROUND: This review describes the safety of deferoxamine (DFO), deferiprone (DFP), deferasirox (DFX) and combined therapy in young patients less than 25 yr of age with haemoglobinopathies. METHODS: Searches in electronic literature databases were performed. Studies reporting adverse events associated with iron chelation therapy were included. Study and reporting quality was assessed using AHRQ Risk of Bias Assessment Tool and McMaster Quality Assessment Scale of Harms. Prospective clinical studies were pooled in a random-effects meta-analysis of proportions. RESULTS: Safety data of 2040 patients from 34 studies were included. Ninety-two case reports of 246 patients were identified. DFX (937 patients) and DFP (667 patients) possess the largest published safety evidence. Fewer studies on combination regimens are available. Increased transaminases were seen in all regimens (3.9-31.3%) and gastrointestinal disorders with DFP and DFX (3.7-18.4% and 5.8-18.8%, respectively). Therapy discontinuations due to adverse events were low (0-4.1%). Reporting quality was selective and poor in most of the studies. CONCLUSION: Iron chelation therapy is generally safe in young patients, and published data correspond to summary of product characteristics. Each iron chelation regimen has its specific safety risks. DFO seems not to be associated with serious adverse effects in recommended doses. In DFP and DFX, rare, but serious, adverse reactions can occur. Data on combined therapy are scarce, but it seems equally safe compared to monotherapy.
EVALuna2:34283